CAD/CAE method of solving the hydrodynamic problem while developing powerful electronic devices - Trofimov, V. E.; Pavlov, A. L.; Mamykin, Y. G. (Technology and design in electronic equipment, 2018)
The article presents examples of the solution of the hydrodynamic problem that arises in the development of powerful electronic devices requiring liquid cooling using the CAD/CAE modeling method. The authors consider poorly documented or undocumented features of such solution based on the use of free software packages — SALOME, OpenFOAM and ParaView for the CAELinux operating system platform.